Magnetic properties of spinel-type oxides NiMn2-xMexO4 - Pena, O.; Moure, C.; Bodenez, V.; Cailleaux, X.; Piriou, B.; Ortiz, J.; Zúñiga, G.; Gautier, J. L.; Lisboa Filho, Paulo Noronha [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2005)
New materials, based on the well-known spinel compound NiMn 2O4, have been synthesized and characterized from the magnetic point of view. The manganese cation was partially substituted in the general formula NiMn2-xMexO4, by nonmagnetic and magnetic elements, such as Me = Ga, Zn, Ni and Cr (0 × 1). Prior to the determination of their magnetic properties, the non-substituted spinel NiMn2O4 was carefully characterized and studied as a function of the oxygen stoichiometry, based on the influence of the annealing atmosphere and quenching rate. The ferrimagnetic character was observed in all samples, with a paramagnetic-to-ferromagnetic transition temperature T c stabilized at 110 K, and well defined long-range antiferromagnetic interactions at lower temperatures, which depend on the applied field and the substitute concentration. © 2006 Sociedad Chilena de Química.
Keywords: Ferrimagnetic properties; Magnetic exchange; Magnetic oxides; Spinels